Profiling and characterizing of banana (Musa paradisiaca) flower bracts-based bioplastic with sorbitol as a plasticizer - Tri Suryandari, Ervin; Hadi Kusuma, Hamdan; Kustomo; Ebit Nugroho, Deni; Mujiasih (Al-Kimia, 2025)
Banana flower bracts (BFB) are a promising source of starch as a bioplastic material. However, starch-based bioplastics products are primarily stiff and rigid to shape. Polyvinyl alcohol (PVA) may improve the elasticity and increase force resistance of starch-based bioplastics. Therefore, this study aims to analyze the characteristics and determine the optimal combination of BFB starch and PVA concentration for bioplastic production. The BFB were chopped and boiled until soft, soaked in sodium bisulfite solution for 30 minutes, and dried to produce fine powder. The powder was macerated in clean water for two days to produce starch, which was then combined with 0.5 chitosan and various concentrations of PVA. Physical characteristic tests, including Force, tensile strength, elongation, and biodegradation, were measured to determine the best composition. This study found the combination of 0.5 gr of BFB starch, 0.5 gr of chitosan, and 10 ml of PVA improved the capability of bioplastic to hold more than 13 N and tensile strengths up to 25 MPa. Furthermore, increasing BFB concentration is in line with enhanced durability; however, it reduces flexibility. Conversely, PVA significantly increased plasticity and elasticity while maintaining high biodegradability (61.2% per day).